Analisis Pengaruh Profitabilitas, Leverage dan Dividend Payout Ratio Terhadap Akrual Diskresioner dan Perataan Laba dengan Kepemilikan Manajerial Sebagai Faktor Pemoderasi - MF Christiningrum; Dewi Aisyah (Jurnal Keuangan dan Perbankan, 2014)
The purpose of this study is to examine whether the profitability, leverage and dividend payout ratio affect the quality of corporate profits or earnings. Manufacturing companies listed in the Indonesia Stock Exchange are tested on their quality of earnings for years 2008-2012 using the proxy for discretionary accruals and income smoothing. In addition to testing the effects, this paper is also aimed in testing the existence of managerial stock ownership as a moderating factor. The results showed that through the use of debt and dividend payout ratio, the profitability of a company is significantly influenced by the quality of its earnings. The decline in profitability and the use of leverage and distribution of dividends affect the discretionary accruals of the company. However, only the dividend distribution triggers the income smoothing. The existence of managerial ownership as moderating factors can weaken the relationship between profitability, leverage and dividend payout ratio on earnings quality. It is seen from the declining significance level of leverage that is proxied by the debt-to-equity ratio, and dividend payout ratio on discretionary accruals, as well as profitability that is proxied by return on assets, and dividend payout ratio on income smoothing.